MAINTENANCE OF SPLIT WALL TYPE AC COOLING SYSTEM FOR THE CONVENIENCE OF WORSHIP IN AL-MADINAH AL-MUNAWWAROH PERUM. SUNRISE GARDEN BUKIT PUTRA CILEUNGSI WEST JAVA: PERAWATAN SISTEM PENDINGIN AC TYPE SPLIT WALL UNTUK KENYAMANAN IBADAH DI AL-MADINAH AL-MUNAWWAROH PERUM. SUNRISE GARDEN BUKIT PUTRA CILEUNGSI JAWA BARAT - Retno Indriyani Kusuma; Intalarasati G; Goklas J. Sirait; Yulianus Beatriksan (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The cooling system (AC) nowadays is included in the category of basic needs, especially for tropical climate areas such as Jakarta and many other areas in Indonesia. The use of AC provides many benefits for human life, namely providing comfort during work activities thereby increasing productivity and maintaining the health of the human body. One type of AC cooler that is often used by the public is the Split wall (non-inverter) type AC because it has several advantages, including the price is cheaper and the installation is quite easy. Like most other electronic products, the air conditioner must also be maintained regularly, according to product guidelines and usage time levels, so that the air conditioner can work optimally without problems and extend the life of the air conditioner